Pengalaman Pasien ACS (Acute Coronary Syndrome) yang Menjalani PCI (Percutaneous Coronary Intervention) - Indri Wahyuningsih; Nur Azizah Azzahra; Anis Ika Nur Rohmah; Zaqqi Ubaidillah (PROFESSIONAL HEALTH JOURNAL, 2023)
Background: Cardiovascular disease is one of the non-communicable diseases that has a high prevalence in the world. According to WHO (World Health Organization), data the highest cause of death is ischemic heart disease, which is 16%, which caused 8.9 million deaths in 2019. ACS (Acute Coronary syndrome) is one of the main cardiovascular diseases that has a high mortality rate. And is the leading cause of death worldwide. Data reported by the Ministry of Health 2019, stated that the prevalence of ACS (Acute Coronary Syndrome) diagnosed by health workers reached 1,5% of other non-infectious diseases, with a mortality prevalence of 12.9% from other causes of death. One of the alternative procedures for ACS (Acute Coronary Syndrome) patients is the PCI (Percutaneous Coronary Intervention) procedure with the installation of a heart ring or stent. In an explanation by a heart and blood vessel specialist at RSUD dr. Iskak, dr. Arif Wibisono, SP. FIHA said patients who underwent PCI (Percutaneous Coronary Intervention) procedures were heart patients with characteristics of the patient’s condition that did not improve or even worsen. Assume that patients with ACS (Acute Coronary Syndrome) would be better off if a PCI (Percutaneous Coronary Intervention) procedure was performed instead of only being given blood clotting drugs. This study aimed to explore the experiences of ACS (Acute Coronary Syndrome) patients undergoing PCI (Percutaneous Coronary Intervention) procedures. The method used in this research is a qualitative method using a case study research strategy, research by testing the validity of data by triangulating sources and analyzing data using domain analysis. The results of this study obtained 2 themes, 1) anxiety with the sub-theme feeling of anxiety before the PCI procedure, 2) Ease of health facilities with the sub-theme of health facilities obtained.